Microbiological features and crevicular fluid aspartate aminotransferase enzyme activity in early onset periodontitis patients - (:unkn) unknown (MUNKSGAARD INT PUBL LTD, 1999)
Gingival crevicular fluid (GCF) reflects the immune and inflammatory reactions and the specific host-microbe interactions that lead to periodontal diseases. Aspartate aminotransferase enzyme (AST) is one of the components of GCF that is released as a result of cell death. In this study, periodontal sites (4 sites/patient) with a probing depth of greater than or equal to 5 mm in early onset periodontitis (EOP) patients were first examined for the AST levels in GCF by the Periogard(TM) periodontal tissue monitor. To be eligible for the study, each of the patients had at least I AST positive site with clinical inflammatory changes (AST+, CIC+) and 1 AST negative site with no or minimum clinical inflammatory changes (AST-, CIC-). In 15 EOP patients who met the entry criteria, 30 AST+, CIC+ sites (Ist group) and 19 AST-, CIC- sites (2nd group) were evaluated for microbiological variables. Certain microbial species, including Porphyromonas gingivalis, Actinobacillus actinomycetemcomitans and Prevotella intermedia were detected more frequently (p<0.001, p<0.001 and p<0.05, respectively) in the Ist group, while gram-positive facultative organisms such as Actinomyces species were found more often (p<0.001) in the 2nd group. Parallel to the AST levels, the 2nd group had a lower number of total bacteria and proportion of obligate anaerobic and capnophilic micro-organisms than the first group (p<0.05 and p<0.05, respectively). Within the scope of this study, AST activity and microbiological data were found in agreement in the examined groups. These findings are encouraging and indicate the need for further studies to evaluate the ability of the AST test to differentiate the microbial flora of progressing sites and those that are inflamed, but not progressing.
Keywords: aspartate aminotransferase; gingival crevicular fluid; microbiology; early onset periodontitis; BLACK-PIGMENTED BACTEROIDES; MULTICENTER CLINICAL-TRIAL; ACTINOBACILLUS-ACTINOMYCETEMCOMITANS; JUVENILE PERIODONTITIS; ADULT PERIODONTITIS; PORPHYROMONAS-GINGIVALIS; IMMUNOLOGICAL FEATURES; TISSUE DESTRUCTION; AST LEVELS; DISEASE